Original articleEvaluation of oxidative and nitrosative stress in relapsing remitting multiple sclerosis: effect of corticosteroid therapy - Seven, Arzu; Aslan, Mahmure; İncir, Said; Altıntaș, Ayșe (Folia Neuropathologica, 2013)
This study is designed to evaluate the roles of oxidative and nitrosative stress in serum and cerebrospinal fluid (CSF) of relapsing remitting multiple sclerosis (RRMS) patients. Oxidative stress markers thiobarbituric acid reactive substances (TBARS), 8-epi-PGF2α, conjugated diene and nitrosative stress markers nitrotyrosine, nitrit-nitrate were analysed in serum and CSF of 20 newly diagnosed RRMS patients before and after methyl prednysolone (MP) therapy (1000 mg/day i.v. , for 5 days) and in healthy control group.TBARS and conjugated diene were analysed spectrophotometrically, nitrite-nitrate fluorometrically, 8-epi-PGF2α and nitrotyrosine were measured by ELISA. Serum conjugated diene (p < 0.001) and 8-epi-PGF2α (p < 0.05) levels were significantly higher in RRMS patients before MP therapy with respect to control group. MP therapy caused a significant decrease only in 8-epi-PGF2α level (p < 0.05). Serum nitrotyrosine levels were significantly lower in RRMS patients both before (p < 0.001) and after (p < 0.001) MP therapy with respect to controls. Serum nitrite-nitrate levels were significantly lower (p < 0.05) in RRMS patients before therapy compared to controls. Nitrotyrosine and nitrite-nitrate levels in CSF of RRMS patients were significantly higher (p < 0.001) before therapy compared to normal pressure hydrocephalia control group. Our findings reveal increased oxidative stress in serum of RRMS patients and the benefical role of MP therapy in relieving oxidative stress.As to nitrosative stress, nitrotyrosine and nitrite-nitrate levels were increased in CSF and decreased in serum.